Purifikasi Katekin dari Ekstrak Gambir (Uncaria gambir Roxb.) - Arifayu Addiena Kurniatri; Novi Sulistyaningrum; Lina Rustanti (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Uncaria gambir Roxb., one of native plants of Indonesia contains high levels of catechins. Catechins are very potential to be used for medicinal raw materials because theirs effects are proven to be antibacterial, antiviral, and antidyslipidemic. Derivatization of catechin can be developed to produce drug compounds that are effective as antiviral agents for HIV. Derivatization process needs pure catechin isolate as a starting material in order to obtain maximum result so that the isolation process is one of the important stages. In this study, isolation and purification of catechin isolate from Uncaria gambir Roxb. extract was carried out, which will then be the starting material in the derivatization of catechin. Gambir extract used for catechin isolation was a quality 1 gambir extract obtained from Padang, West Sumatra. Gambier extract is characterized according to the standard method stated in Farmakope Herbal Indonesia. Isolation of catechin from gambir extract was done by percolation method using ethyl acetate solvents. Pure catechin isolate was obtained using a vacuum liquid chromatograpy method with a series of solvent hexane and ethyl acetate gradients. Catechin purification was monitored using Thin Layer Chromatography (TLC) method with eluent chloroform:ethyl acetate:formic acid (5:4:1, then identified using High Performance Liquid Chromatography (HPLC), Nuclear Magnetic Resonance (NMR) Spectroscopy, and Liquid Cromatography- Mass Spectroscopy (LC-MS). The purity of catechin isolate obtained was 99.80%± 0.132. Abstrak Uncaria gambir Roxb., salah satu tanaman asli Indonesia yang mengandung katekin dengan kadar yang tinggi. Katekin sangat potensial digunakan untuk bahan baku obat karena efeknya terbukti sebagai antibakteri, antivirus, dan antidislipidemia. Derivatisasi katekin dapat dikembangkan untuk menghasilkan senyawa obat yang efektif sebagai antivirus untuk HIV. Untuk derivatisasi ini diperlukan isolat katekin murni sebagai starting material agar diperoleh hasil yang maksimal sehingga proses purifikasi isolat merupakan salah satu tahap yang penting. Dalam penelitian ini dilakukan isolasi dan pemurnian isolat katekin dari ekstrak Uncaria gambir Roxb. yang selanjutnya akan menjadi bahan awal dalam derivatisasi katekin. Ekstrak gambir yang digunakan untuk isolasi katekin adalah ekstrak gambir kualitas 1 yang diperoleh dari Padang, Sumatera Barat. Ekstrak gambir dikarakterisasi sesuai dengan metode standar yang tertera dalam Farmakope Herbal Indonesia. Isolasi katekin dari ekstrak gambir dilakukan dengan metode perkolasi menggunakan pelarut etil asetat. Isolat katekin murni diperoleh menggunakan metode kromatografi cair vakum (KCV) dengan serangkaian gradien pelarut heksana dan etil asetat. Pemurnian katekin dimonitor menggunakan metode kromatografi lapis tipis (KLT) dengan eluen kloroform : etil asetat : asam format (5:4:1), kemudian diidentifikasi menggunakan High Performance Liquid Chromatography (HPLC), spektroskopi Nuclear Magnetic Resonance (NMR), dan Liquid Cromatography-Mass Spectroscopy (LC- MS). Kemurnian isolat katekin yang didapatkan 99,80%± 0,132.